Model of social media crisis communication for predicting public resilience - Ali, Umar Bukar (2021)
Many scholars have proved the application and effectiveness of technology in crisis management and communication. In particular, social media has been effective for both formal and informal communication during and after a crisis. However, what matters to people when a crisis occurs is recovery, which involves resilience. Hence, researchers must begin to experiment on how social media is helping people to recover from a crisis and what social media task helps people recover quickly. Therefore, this study investigates existing crisis communication models from literature to identify commonalities within these models then proposes a social media crisis communication and resilience model (SMCCR). Moreover, the objectives of the study are to find out the impact of crisis response on social media interaction and public resilience, to determine the direct impact of social media interaction on public resilience, and to investigate the mediating effect of social media interaction on public resilience and the mediating effect crisis response on public resilience. An operational research framework comprising literature review, model development, model validation, and result was adopted to address the research problem. An SMCCR model was derived based on the synthesis and thematic analysis of existing theoretical models. Specifically, situational crisis communication theory (SCCT), an interactive crisis communication model (ICCM), STREMII model, and social media disaster resilience model (SMDR) was adapted. A confirmatory study that involved an expert evaluation, pilot test, and a survey was conducted. The expert evaluation was conducted in two rounds with four experts, respectively. The first round was revised due to aggregated ratings to improve the agreement among the experts. Subsequently, based on the feedback of the experts, the questionnaire items were revised. 34 items were finalized from the expert review and analyze by content validity index (CVI) and modified kappa statistics. After passing the validation test, the instruments were pre-tested by 32 participants. The responses were assessed based on Cronbach alpha, regression model, and the hypothesis was independently evaluated in process macro models. Afterward, a survey was conducted with a population of social media users who had experienced the Covid-19 crisis and were practicing physical distancing in Malaysia. The final sample consists of 393 responses that were analyzed using variance-based structural equation modeling (PLS-SEM). The reliability and validity of the SMCCR model were demonstrated through a confirmatory study. The findings revealed the relationships among model constructs, namely: crisis, crisis response, social interaction, and resilience. In this regard, all eight research hypotheses were supported. Descriptive statistics were also used to present the summary of the data collected in the study. The results of the investigation demonstrated the impacts of the SMCCR model in the real world and elucidated how it can assist crisis management organizations in understanding the impact of social media crisis responses and social interaction to improve the ability of the people to recover from the crisis. The study makes theoretical contributions by examining the role of social media crisis communication through crisis response and social interaction in addressing the impact of crisis communication on public resilience based on the theoretical lens of SCCT, ICCM, and SMDR. Likewise, the activities of crisis management to improve the ability of the people to recover from crisis quickly, the relationship between crisis, crisis response, social interaction, and resilience proves to be effective. This study offers empirical evidence that social media crisis communication influence people’s ability to recover from the crisis through the mediation of crisis responses and social media interaction.